Comparative analysis of a sex chromosome from the blackchin tilapia, Sarotherodon melanotheron. (December 2016) - Gammerdinger, William; Conte, Matthew; Baroiller, Jean-François; D'Cotta, Helena; Kocher, Thomas
Abstract Background Inversions and other structural polymorphisms often reduce the rate of recombination between sex chromosomes, making it impossible to fine map sex-determination loci using traditional genetic mapping techniques. Here we compare distantly related species of tilapia that each segregate an XY system of sex-determination on linkage group 1. We use whole genome sequencing to identify shared sex-patterned polymorphisms, which are candidates for the ancestral sex-determination mutation. Results We found thatSarotherodon melanotheron segregates an XY system on LG1 in the same region identified inOreochromis niloticus . Both species have higher densities of sex-patterned SNPs, as well as elevated number of ancestral copy number variants in this region when compared to the rest of the genome, but the pattern of differentiation along LG1 differs between species. The number of sex-patterned SNPs shared by the two species is small, but larger than expected by chance, suggesting that a novel Y-chromosome arose just before the divergence of the two species. We identified a shared sex-patterned SNP that alters aGata4 binding site nearWilms tumor protein that might be responsible for sex-determination. Conclusions Shared sex-patterned SNPs, insertions and deletions suggest an ancestral sex-determination system that is common to bothS. melanotheron andO. niloticus . Functional analyses are needed to evaluate shared SNPs near candidate genes that might play a role in sex-determination of these species. Interspecific variation in the sex chromosomes of tilapia species provides an excellent model system for understanding the evolution of vertebrate sex chromosomes.